On collectionwise Hausdorff bitopological spaces - Bouseliana, Hend M.; Kilicman, Adem (Institute for Mathematical Research, Universiti Putra Malaysia, 2012)
In this work, we introduce the concept of collectionwise Hausdorff bitopological spaces by using p1 -open sets. Further, we also study the relations of collection wise Hausdorff spaces with some separation axioms and paralindeloff bitopological spaces.